Hubungan Jenis Kelamin Terhadap Tingkat Kemandirian Dalam Merawat Diri Pada Lanjut Usia - meynur rohmah; Dewi Nur Puspita Sari; Tuti Wahyuningsih; Tika Fatmala (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
The elderly (elderly) when compared with other age groups have their own uniqueness, this can be known by studying gerontic theories and the changes that occur. The purpose of this study was to determine the relationship between gender and the level of independence in self-care in the elderly. This research is a descriptive correlation study with a cross-sectional approach, where the measurement of the independent variable and the dependent variable is carried out simultaneously. Measurement of variables was done by direct interview using a questionnaire. The results of the study were based on the most elderly aged 60-74 years as many as 10 people (55.6%), based on gender the number of elderly men and women were the same, namely 9 elderly men (50%). ), elderly women 9 people (50%), based on education are high school graduates as many as 8 people (44.4%), based on marital status are widowers/widows 10 people (55.6%), from the results of bivariate analysis that there is no There is a significant relationship between gender and the level of independence in self-care in the elderly. The conclusion of the study, there is no relationship between gender and the level of independence in self-care in the elderly. It is recommended for the elderly that the orphanage administrators teach or inform the elderly who are still independent in doing ADL (Activity Daily Living) to help the elderly who are not or less independent in doing ADL (Activity Daily Living). Keywords: elderly, gender, independence